Changes in the Epidemiology and Causative Pathogens of Meningitis in Children After the Outbreak of the Coronavirus Disease 2019: A Multicenter Database Study - Lee, Jooyoung; Choi, Arum; Kim, Kyunghoon; Bin, Joong Hyun; Eom, Tae Hoon; Yoo, Il Han; Yoon, Da Hye; Kim, Sukil; Kim, Young Hoon (Frontiers in Pediatrics, 2022)
With the outbreak of the COVID-19 pandemic, non-pharmaceutical interventions such as social distancing have been implemented worldwide, and a decrease in other infectious diseases has been reported as an unexpected benefit. However, to date, studies are lacking regarding the effects of the COVID-19 pandemic on neuroinfectious diseases; therefore, we aimed to determine the effects of the COVID-19 pandemic on the incidence of meningitis, which is the most common infectious disease in children. This retrospective study used electronic medical record data from five university hospitals located in metropolitan cities in Korea. This study included patients aged < 18 years who were diagnosed with meningitis between January 2017 and December 2020. We analyzed the clinical characteristics of patients with meningitis and changes in the incidence and causative pathogens of meningitis before and after the COVID-19 outbreak. The study included 677 patients with meningitis. Following the outbreak of COVID-19 in Korea in January 2020, the incidence of childhood meningitis significantly decreased and seasonal changes noted yearly disappeared. There was a difference in the age distribution of patients with meningitis. The incidence of meningitis decreased significantly in children aged > 5 years, and the incidence in children < 5 years of age relatively increased (p<0.001). In addition, there was a notable decrease in the cases of suspected meningitis (p<0.001). The incidence of enteroviral meningitis, the most common cause of meningitis, significantly decreased. After the COVID-19 outbreak, the incidence of childhood meningitis significantly decreased with the implementation of non-pharmaceutical interventions. Absence of enteroviral meningitis and decrease in the proportion of patients aged ≥ 5 years with meningitis having mild symptoms were noted. Consequently, it can be concluded that the NPIs instituted to prevent the spread of COVID-19 had some effect on reducing the incidence of meningitis.